Comparison of Informational and Educational Resource Provision for Individuals Living With Traumatic Brain Injury Based on Language, Nativity, and Neighborhood. Issue 2 (2nd March 2023) - Wilson, Judith; McGiffin, Jed N.; Smith, Michelle; Garduño-Ortega, Olga; Talis, Elina; Zarate, Alejandro; Jenkins, Natalie; Rath, Joseph F.; Bushnik, Tamara
Abstract : Objective: To examine a resource provision program for individuals living with moderate-to-severe traumatic brain injury (TBI), using a comparison of the resources provided across social differences of language, nativity, and neighborhood. Setting: The Rusk Rehabilitation TBI Model System (RRTBIMS) collects data longitudinally on individuals from their associated private and public hospitals, located in New York City. Participants: A total of 143 individuals with TBI or their family members. Design: An observational study of relative frequency of resource provision across variables of language, nativity, and neighborhood, using related-samples nonparametric analyses via Cochran's Q test. Main Measures: Variables examined were language, place of birth, residence classification as medically underserved area/population (MUA), and resource categories. Results: Results indicate that US-born persons with TBI and those living in medically underserved communities are provided more resources than those who are born outside the United States or reside in communities identified as adequately medically served. Language was not found to be a factor. Conclusion: Lessons learned from this research support the development of this resource provision program, as well as guide future programs addressing the gaps in health information resources for groups negatively impacted by social determinants of health (SDoH). An approach with immigrant participants should take steps to elicit questions and requests, or offer resources explicitly. We recommend research looking at what interpreter strategies are most effective and research on SDoH in relation to the dynamic interaction of variables in the neighborhood setting.